Seasonal and daily formation of the shading zone in the edge part of dense field shelterbelts - Sydorenko, S. V.; Korsovetskyi, V. O.; Sydorenko, S. H.; Hladun, H. B. (Forestry and Forest Melioration, 2020)
Introduction It is known that forest shelterbelts provide favourable conditions for increasing the overall productivity of agricultural lands. However, their border parts have a negative effect on the growth and development of crops due to the shadow created by the tree crowns. The ecological conditions of the suppression zone are characterized by poorer lighting, air stagnation and other negative factors that produce a greenhouse effect during a warm growing season, which affects the crop development. Light regime modelling during the growing season in the areas adjacent to the shelterbelts is important for the rational management practices, which must be differentiated for different parts of the field. The obtained results will allow optimizing the usage of various physiological properties of crops for different parts of the field. Materials and Methods Theoretical calculations of solar radiation parameters during the research were used. For calculations, a typical spatial location of primary (from S–W to N–E) and secondary field shelterbelts located in the Left-Bank Forest-Steppe were applied. Their forestry and agroforestry characteristics were also taken into account. Changes in the light regime caused by the barrier action of the shelterbelts were analyzed due to changes in the phytomass of maize (Zea mays L.) considering the distance to the shelterbelt. The theoretical calculations were compared with the field data on the distribution of maize phytomass in the field. Results During a growing season, the eastern part of the field in the distance of 0–2.5 H from a shelterbelt (where H is an average tree height in the shelterbelt) receives per day 13.8% less solar energy than the western part, and 24.2% less compared to the open field. The amount of solar energy received by a field depends on the direction and height of the shelterbelt, the time of day, as well as the season. The location of shelterbelts at certain angles relative to the latitude and longitude leads to more complex situations, and represents intermediate stages of illumination between N–S and W–E. A significant weakening in the solar radiation inflow to the field was observed to the part of the near-edge zone of the shelterbelt of 1.5–2 H, i. e. for the distance from the shelterbelt of 40 m at an average tree height of 20 m. The shadow formation and its movement during daylight hours accounts for an uneven distribution of light and solar energy at a distance of 2.5 H from the shelterbelt. If a shelterbelt is located from east to west (normally secondary shelterbelt), the southern part of the field near the shelterbelt receives much more energy and is practically not in shading (96.9% compared to the open field). The northern part receives 25% less solar energy in spring, 17% less in summer, and 42% less in autumn (September). The areas of the field in the northern part of the shelterbelt obtain different amounts of light: 0.5 H – 28.4%; 1 H – 71%; 1.5 H – 94%; 2 H – 99%; 2.5 H – 99%. Instead, the areas on the southern side have the following distribution: 0.5 H – 92%; 1 H – 96.7%, 1.5 H – 98.5%; 2 H – 99%; 2.5 H – 99.8%. The maize phytomass increased with the distance from shelterbelts from 0 to 25.1 tonnes per ha. A sharp decrease in phytomass is observed at a distance of 0–30 m from the shelterbelt which corresponds to 1.5–2 H. The regression analysis showed that the aboveground phytomass variation is for 89–97% (R2 = 0.97, p = 0.05) dependent on the distance from the shelterbelt (for the interval of 0–1.5 H). On the southern side of the shelterbelt, the suppression zone for maize makes up 22–25 m, i. e. up to 1.2 H. From the eastern part of the shelterbelt, the suppression zone reaches 1.5 Н. Thus, a significant effect of shading is observed up to the distance of 30–35 meters from the shelterbelt. Conclusions For typical shelterbelts in Left-Bank Forest-Steppe (“dense” type), the indicators of seasonal and daily dynamics of shadow formation and the degree of solar energy undersupply to the field surface depend on the distance from a shelterbelt and fields’ spatial location. A significant effect of shading from a shelterbelt was found to extend up to a distance of 1.2–1.5 H. The length of the shading zone depends on the protective height of the shelterbelt and its spatial location. The strongest shading impact is observed on the northern side of the shelterbelt while the slightest one, on the southern side. The study revealed that depending on the spatial location of the shelterbelt, such zones extend to a distance of up to 1.2–1.5 H. It was found that the allocation of the suppression zone in absolute values is incorrect. Moreover, such zones are determined by the shelterbelt height and tree crown size. The edge of the crown projection towards the field should be taken as the starting point for suppression zone calculation. 11 Figs., 2 Tables, 31 Refs. Key words: shelterbelts, shading, depression zone, light, shadow, energy, height, competition, phytomass.